Tahara [videorecording (DVD)] - Zeidman, Jess; DeFreece, Madeline Grey; Sennott, Rachel; Taveras, Daniel; Azoulay, Shlomit; Quigley, Bernadette; Lester, Jenny; Lawson, Melissa Juliet; Anthony, Ellie; Weiss, Keith; Wender, Rachel; Taylor, Lynne (Actress); et al. (Film Movement, 2022)
"Carrie Lowstein (Madeline Grey DeFreece) and Hannah Rosen (Rachel Sennott) have been inseparable for as long as they can remember. When their former Hebrew school classmate, Samantha Goldstein, commits suicide, the two girls go to her funeral as well as the "Teen Talk-back" session designed to be an opportunity for them to understand grief through their faith. But, after an innocent kissing exercise turns Carrie's world inside out, the best friends find themselves distracted by the teenage complications of lust, social status, and wavering faith"--Film Movement WWW site (viewed March 25, 2022).